MORPHOLOGICAL AND SEMANTIC ANALYSIS OF PASSIVE AND DOUBLE VERBS AND PASSIVE VERBS USED IN THE WORK (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Among these, verbs are central to Arabic grammar. Because too many nouns in Arabic are also mostly made from the verb stem. In Arabic, as in other languages, independent words that represent the work-action of the subject are called verbs.1 in Arabic, the verb is distinguished by its personification and number Tusk. Arab nahwists place the verb in contrast to nouns and loadings.